2‐Arachidonoyl‐glycerol‐ and arachidonic acid‐stimulated neutrophils release antimicrobial effectors against E. coli, S. aureus, HSV‐1, and RSV. Issue 2 (1st February 2013) - Chouinard, François; Turcotte, Caroline; Guan, Xiaochun; Larose, Marie‐Chantal; Poirier, Samuel; Bouchard, Line; Provost, Véronique; Flamand, Louis; Grandvaux, Nathalie; Flamand, Nicolas
Abstract : Neutrophils activated with nanomolar concentrations of 2‐arachidonoyl‐glycerol or arachidonic acid, release antimicrobial effectors, unraveling these lipids as possible regulators of host defense in vivo. Abstract : The endocannabinoid 2‐AG is highly susceptible to its hydrolysis into AA, which activates neutrophils through de novo LTB4 biosynthesis, independently of CB activation. In this study, we show that 2‐AG and AA stimulate neutrophils to release antimicrobial effectors. Supernatants of neutrophils activated with nanomolar concentrations of 2‐AG and AA indeed inhibited the infectivity of HSV‐1 and RSV. Additionally, the supernatants of 2‐AG‐ and AA‐stimulated neutrophils strongly impaired the growth of Escherichia coli and Staphylococcus aureus . This correlated with the release of a large amount (micrograms) of α‐defensins, as well as a limited amount (nanograms) of LL‐37. All the effects of AA and 2‐AG mentioned above were prevented by inhibiting LTB4 biosynthesis or by blocking BLT1 . Importantly, neither CB2 receptor agonists nor antagonists could mimic nor prevent the effects of 2‐AG, respectively. In fact, qPCR data show that contaminating eosinophils express ∼100‐fold more CB2 receptor mRNA than purified neutrophils, suggesting that CB2 receptor expression by human neutrophils is limited and that contaminating eosinophils are likely responsible for the previously documented CB2 expression by freshly isolated human neutrophils. The rapid conversion of 2‐AG to AA and their subsequent metabolism into LTB4 promote 2‐AG and AA as multifunctional activators of neutrophils, mainly exerting their effects by activating the BLT1 . Considering that nanomolar concentrations of AA or 2‐AG were sufficient to impair viral infectivity, this suggests potential physiological roles for 2‐AG and AA as regulators of host defense in vivo.